ANALISIS BUTIR SOAL UJIAN SEMESTER GENAP MATA PELAJARAN GEOGRAFI - Rima Melati; Sudarmi Sudarmi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2014)
The objective of the research was to analyze the questions of the second semester final test of Geography for the students of grade X at SMA Negeri 1 Natar in 2012/2013 including validity, reliability, difficulty level, distinguishing factor efficiency,  and answer’s pattern. This research used descriptive method. The result showed that the questions’ qualities were as follow: 1) As seen from the validity of each questions it was found that there were 8 or 16% questions were valid and 42 or 84% questions were not valid. 2) The reliability was classified as good enough with coefficient was 0,425 or 42,5%. 3) The questions’ difficulty level showed that there were 1 or 2% questions which were categorized as easy.  4) The distinguishing factors efficiency that was observed showed that there were 10 or 20% questions had good distinguishing factors. 5) As seen from the answers’ pattern it was known that generally all the distractors of each questions were good.Penelitian ini bertujuan untuk menganalisis butir soal Ujian Semester Genap Mata Pelajaran Geografi Siswa Kelas X SMA Negeri 1 Natar Tahun Pelajaran 2012/2013 meliputi validitas, reliabilitas, tingkat kesukaran, daya pembeda dan pola jawaban. Penelitian ini menggunakan metode deskriptif. Hasil analisis yang dilakukan menunjukkan bahwa kualitas soal yang digunakan, 1) Dilihat dari validitas tiap butir soal terdapat 8 atau 16% butir soal dikatakan valid dan 42 atau 84% yang tidak valid. 2) Reliabilitas termasuk dalam klasifikasi cukup dengan koefisien 0,425 atau 42,5%. 3)Tingkat kesukaran butir soal terdapat 1 atau 2% kategori mudah. 4) Ditinjau daya pembeda terdapat 10 atau 20% butir soal memiliki daya pembeda baik. 5) Dilihat dari pola jawaban diketahui bahwa secara umum semua pengecoh (distractor) pada butir soal tersebut sudah berfungsi dengan baik.Kata kunci: analisis butir soal, mata pelajaran geografi, ujian semester.